Comparison of Nose Wipes, Stall Sponges, and Air Samples with Nasal Secretions for the Molecular Detection of Equine Influenza Virus in Clinically and Subclinically Infected Horses - Nicola Pusterla; Kaila Lawton; Samantha Barnum; K. Gary Magdesian (Viruses)
In recent years, the use of non-invasive host and environmental samples for the detection and monitoring of equine respiratory pathogens has shown promise and a high overall agreement with the gold standard of nasal secretions. The present study looked at comparing nose wipes, stall sponges, and air samples with nasal swabs collected from 27 horses involved in an equine influenza (EI) outbreak. The outbreak involved 5 clinical, 6 subclinical, and 16 uninfected horses. Samples sets were collected at the onset of the index case and retested every 2–3 days thereafter until all horses tested qPCR-negative for EI virus (EIV). Nose wipes and stall sponges identified EIV in all clinical cases, and air samples identified EIV in 4/5 clinical horses. The overall agreement with all nasal swabs collected from clinical cases was 89% for nose wipes, 78% for stall sponges, and 44% for air samples. Due to the shorter shedding time in subclinical cases, nose wipes and stall sponges detected EIV in 5/6 and 4/6 subclinical horses, respectively. Only one single air sample tested qPCR-positive for EIV in a subclinical shedder. When compared to the gold standard of nasal secretions in subclinically infected horses, the overall agreement was 54% for stall sponges, 50% for air samples, and 45% for nose wipes. The collection of non-invasive contact and environmental samples is a promising alternative to nasal swabs for the detection of EIV in clinically and subclinically infected horses. However, they should always be considered as a second-choice sample type to the more accurate nasal swabs and used to test refractory horses or large populations during outbreaks. Further, the pooling of identical or different samples collected from the same horse for the qPCR testing of EIV increases the accuracy of detecting EIV, especially in subclinically infected horses.